Pengaruh Gadget Pada Anak di SD Negeri Ema - Ronald Darlly Hukubun; Laury Marcia Chara Huwae; Stefanno M. A. Rijoly; Marcia Lainsamputty; Zusye Latuihamallo; Ruben Mesasnuat (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2024)
The development of media and technology is a challenge for children's development. There are many negative impacts, namely that it can disrupt health and can interfere with development children, prone to crime, can affect children's behavior, difficulty concentrating to the real world, disruption of brain function in children, and can become dependent on gadgets. The role of parents is very important to supervise, control and pay attention all children's activities to see better child development. The method used is the method of counseling about the influence of gadgets on children. The result of this outreach activity is to increase students' understanding of the negative and positive influences of excessive use of gadgets.